(untitled) (Scientific journal of the Fergana State University, 2024)
This article shows the use of metaphors in political texts, focusing on how they shape public perception and influence political discourse. By analyzing a range of political speeches and writings, the research identifies common metaphorical frameworks and explores their cognitive and rhetorical functions. Using a mixed-methods approach, the study combines quantitative analysis of metaphor frequency with qualitative insights into their contextual meanings. The results reveal the prevalence of war, journey, and health metaphors in political language, demonstrating their role in framing political issues and mobilizing public opinion. This analysis underscores the power of metaphors in political communication, highlighting their strategic use in shaping ideologies and persuading audiences.